Historisitas Tradisi Pohon Nangker dalam Mempertahankan Identitas Budaya Lokal di Desa Gapura Tengah - Abd. Halim; Mukhlisi Mukhlisi; Matroni Matroni (CV. ULIL ALBAB CORP, 2025)
This study aims to explore the role of the kapok tree (Ceiba pentandra) as a symbol of cultural identity and tradition in the community of Gapura Tengah Village, as well as the challenges faced in preserving local culture. The research method employed includes in-depth interviews with community members and participatory observation. The findings indicate that the kapok tree serves not only as a natural resource but also as a representation of the values and beliefs of the community. Traditions associated with this tree, such as the lobaran celebration, play a crucial role in transmitting local wisdom values to younger generations and strengthening social bonds among community members. However, challenges to cultural preservation arise due to the influences of globalization and rapid social change. This study recommends that the community continue to engage younger generations in cultural activities and integrate education about local culture into school curricula to maintain the continuity of cultural identity amidst changing times.